Yield, nutrient uptake and economics of direct seeded aerobic rice (Oryza sativa L.) as influenced by seed rate and cultivars - Yadav, Ajit; Singh, D.K.; Kumar, Amit; Chaudhary, S.; Singh, S.; Singh, S.P.; Verma, Gaurav (Annals of Agricultural Research, 2017)
A field experiment was conducted during kharif season of 2014 at N.E. Borlaug Crop Research Centre of G.B. Pant University of Agriculture & Technology, Pantnagar (Uttarakhand) to optimize the seed rate of hybrid and high yielding varieties of rice under direct seeded aerobic condition. Treatments were tested in a split plot design with three replications keeping varieties (PAC-837, DRRH-3 and PD-16) in main-plots and seed rates (15, 25, 35 and 45 kg/ha) in sub-plots. Hybrid varieties DRRH- 3 and PAC-837 performed better with the grain yields (4620 kg/ha and 4554 kg/ha), nutrients uptake 153.2 kg/ha and 148.2 kg/ha) and higher net returns (54,205 and 52,729 Rs./ha) respectively as compared to high yielding variety PD-16 (4408 kg/ha, 144.3 kg/ha and 51,197 Rs./ha). Among the different seed rates tested, seed rate of 35 kg/ha produced more grain yield (4829 kg/ha), nutrient uptake (157.8 kg/ha) and net returns (54,205 Rs./ha) as compared to other seed rates. More yield, nutrient uptake and higher profit from direct seeded aerobic rice can be obtained from hybrid rice varieties with seed rate of 35 kg/ha under Tarai condition of Uttarakhand.